CLINICAL FENOTIP HOZL WITH FREQUENT SHARPENING: AUTHENTICATION, DETERMINATION AND CONSEQUENCES FOR PATIENT - Островський, М. М.; Стовбан, М. П.; Корж, Г. З.; Зубань, А. Б.; Кулинич-Міськів, М. О.; Варунків, О. І.; Бондаренко, Т. Я.; Савеліхіна, О. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Steady progress in understanding of problem of obstructive diseases of lights puts more of open questions new and, that finds the reflection in many publications last years, including in materials of annual congress of European respirator society (European Respiratory Society – ERS), which took place in September, 2014р. in Munich. Presumably, unique, whatever causes disagreements among the researchers of problem of chronic obstructive disease of lights (HOZL), it is necessary to count negative prognoses in relation to his distribution in the nearest decades, exactly both approaches to diagnostics and questions of rational therapy depend from phenotype HOZL, that does the given pathology by one of most problems of health protection.